Analisis Pengaruh Spoiler terhadap Aerodinamika Mobil Jenis Urban dengan Simulasi Computational Fluid Dynamics - Achmad Nadhomul Faidh Al Qodir; Alviani Hesthi Permata Ningtyas (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of spoiler size variations on the Coefficient of Drag (CD) and Coefficient of Lift (CL), as well as to investigate the characteristics of velocity, pressure, and turbulent kinetic energy contours in an urban-type vehicle under various airflow velocities. The research employed a Computational Fluid Dynamics (CFD) simulation approach using ANSYS Workbench software, while the urban-type vehicle model was designed using Autodesk Inventor. Three spoiler dimensions were evaluated, namely 2200 × 500 mm, 2200 × 600 mm, and 2200 × 700 mm, under airflow velocities of 60 km/h, 80 km/h, and 100 km/h. The simulation results indicate that spoiler size variations significantly affect the aerodynamic characteristics of the vehicle. The 2200 × 500 mm and 2200 × 600 mm spoilers exhibited better aerodynamic performance by generating downforce, which contributes to improved vehicle stability. In contrast, the 2200 × 700 mm spoiler produced an increase in Lift Force that may reduce vehicle stability. Furthermore, contour analysis revealed the formation of wake regions and an increase in turbulence intensity behind the vehicle as the spoiler size and airflow velocity increased. Therefore, selecting an appropriate spoiler dimension can improve the aerodynamic performance and stability of urban-type vehicles. Keywords: Aerodynamics, Computational Fluid Dynamics (CFD), Coefficient of Drag (CD), Coefficient of Lift (CL), Spoiler, Urban-Type Vehicle.